Repositioning forward-leaning vehicle occupants with a pre-pretensioner belt and a startle-based warning in pre-crash scenarios. (10th October 2022) - Graci, V.; Griffith, M.; Seacrist, T.; Brase, D.; Mishra, E.; Pipkorn, B.; Lubbe, N.; Arbogast, K.B.
Abstract: Objective: Pre-pretensioner (PPT) seatbelts have been found to be effective in controlling vehicle occupants' motion response to disturbances in optimally positioned occupants, but it is not clear how the PPT performs when the occupant is initially forward leaning. Previous work demonstrated that an acoustic startling pre-stimulus (ASPS) reduced trunk out-of-position in sled-simulated pre-crash maneuvers. Therefore, the aim of this study was to determine if coupling the PPT with the ASPS could reduce the needed magnitude and rate of belt tension of the PPT to reposition forward leaning occupants to their optimal position within the seatbelt. Methods: Sixteen belt-restrained adult human volunteers (8 males and 8 females) restrained by a 3-point seatbelt on a vehicle seat in a forward leaning posture on a sled simulating pre-crash braking (approx. 1 g of maximum acceleration and 0.3 s duration) were exposed to sled perturbations with three belt configurations (low and high force PPT and no PPT), and two warning conditions (ASPS and no-ASPS). Head and trunk positions were extracted from the 3D motion-capture data. Repeated measure ANOVAs were used to understand the effect of sex, PPT, ASPS, and repetition on head and trunk positions. A survival analysis was also performed to understand the probability of the occupants moving rearward in the different conditions. Results: The probability of the head and trunk to move rearward from the initial position was greater with the PPT than without the PPT (p = 0.01) and with the high force level than the low force level (p = 0.01). The interaction effect of ASPS x PPT showed that with no PPT, there was a greater probability for the head to move rearward from the initial position with ASPS than without ASPS (p < 0.03). The trunk shows a similar trend to the head, but the ASPS vs no-ASPS differences were not statistically significant (p = 0.06). No sex differences were found. Conclusions: The PPT, particularly the high level, may be an effective countermeasure on its own to reduce trunk and head out-of-position in forward leaning postures in pre-crash scenarios. The ASPS reduced the occupants' head forward position when the PPT was not available.